2017
DOI: 10.1111/jnu.12326
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Climate Justice, and Environmental Health: Implications for the Nursing Profession

Abstract: Recognizing the negative impacts of climate change on well-being and the underlying socioeconomic reasons for their disproportionate and inequitable distribution can expand and optimize the profession's role in education, practice, research, and policy-making efforts to address climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 4 publications
(3 reference statements)
1
67
0
Order By: Relevance
“…The complexity of the phenomenon of violence in healthcare activities requires simultaneous action on several levels, including educational, organizational, and medical measures; the most effective interventions generally have a participatory, bottom‐up approach, and require several years of work to be fully implemented (Magnavita, 2011). Organizations should invest in supervisor training; indeed, previous studies have shown that managers can be trained to act in a more just manner, and this improves subordinates' attitudes and behavior (Katz, 2018; Nicholas & Breakey, 2017). Such demanding programs are justified in health activities because the ability of nurses to work properly according to professional standards is of crucial importance for the delivery of effective care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the phenomenon of violence in healthcare activities requires simultaneous action on several levels, including educational, organizational, and medical measures; the most effective interventions generally have a participatory, bottom‐up approach, and require several years of work to be fully implemented (Magnavita, 2011). Organizations should invest in supervisor training; indeed, previous studies have shown that managers can be trained to act in a more just manner, and this improves subordinates' attitudes and behavior (Katz, 2018; Nicholas & Breakey, 2017). Such demanding programs are justified in health activities because the ability of nurses to work properly according to professional standards is of crucial importance for the delivery of effective care for patients.…”
Section: Discussionmentioning
confidence: 99%
“… 4 For example, in the United Kingdom of Great Britain and Northern Ireland, nurses and their associations across all levels are addressing climate change by raising awareness and calling for greater climate justice as well as advocating for and implementing climate adaptation and mitigation strategies. 5 The National Health Service recently announced its goal to become net carbon zero by 2040. While professional associations can make positive changes and create awareness, many aspects of climate change adaptation and mitigation can only be addressed by national and subnational policy-makers, for example in the way that health facilities and workers consume energy and food, and use transport and logistics to procure supplies.…”
Section: Primary Care and Public Health Interventionsmentioning
confidence: 99%
“…Nursing has the potential to advocate for social justice for the world’s people by addressing the socioeconomic inequities that determine the impacts of global warming. Nurses have an ethical responsibility to climate justice and advancing policy that protects the world’s most vulnerable as they confront climate change’s life‐threatening sequelae Conceptual model development to understand the predictors and consequences of the human biological response to increasing heat environments; farmworkers exposed to the hazard of heightened heat stress because of global warming require public health interventions to keep them safe and healthy as the climate continues to change …”
Section: The United Nations Sustainable Development Goals: Opportunitmentioning
confidence: 99%
“…Nursing has the potential to advocate for social justice for the world’s people by addressing the socioeconomic inequities that determine the impacts of global warming. Nurses have an ethical responsibility to climate justice and advancing policy that protects the world’s most vulnerable as they confront climate change’s life‐threatening sequelae …”
Section: The United Nations Sustainable Development Goals: Opportunitmentioning
confidence: 99%